CONNOTATIVE MEANING IN ALAN WALKER'S SONG "HERO": A SEMANTIC APPROACH - Ahmad Kirom; FX Sawardi; Supana (English Language Teaching Journal, 2025)
This study aims to describe the connotative meaning of the lyrics of the song "Hero" by Alan Walker using a descriptive qualitative approach. This research describes the phenomenon in depth in song lyrics to understand the implicit messages and connotative meanings contained in them. The main source of data is the lyric text "Hero" obtained from the official digital platform. The data was analyzed through the identification of key words, exploration of denotative and connotative meanings, and association with the main theme of the song. The results of the study show that songwriters use various elements of connotative language to convey messages about struggle, hope, courage, and solidarity in facing life's challenges. The connotative meaning in the lyrics of this song reinforces the main theme about the strength of the individual and the importance of collaboration in achieving common goals. This research contributes to understanding how linguistic elements in song lyrics can construct connotative meanings that are relevant to the emotional, social, and cultural context of the listener. Keywords: connotative meaning, song lyrics, HERO, Alan Walker